Neural activation after maximal isometric contractions at different muscle lengths - Desbrosses, K.; Babault, N.; Scaglioni, G.; Meyer, J. -P.; Pousson, M. (Medicine & Science in Sports & Exercise, 2006)
Purpose: To investigate i) whether neural activation dependence on muscle length is preserved with neuromuscular fatigue and ii) whether fatigue induced by a maximal isometric exercise is muscle length dependent.